2021
DOI: 10.2478/bipca-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Study of Condensation Risk in Ecological Blocks with Recycled Wood Aggregate

Abstract: Concrete is a building material with a continuous demand in the construction industry due to the convenient price-performance ratio. On the other hand, concrete is not an environmentally friendly material. Thus, in order to obtain a sustainable material, wood waste can be recycled and used as light aggregates in the manufacture of precast ecological building blocks. Block walls must satisfy not only structural criteria but also functional requirements. In addition, thermal contribution is important in reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Xue et al [ 25 ] found inappropriate thermal insulation measures may exacerbate the humidity within the building envelope and further induce condensation and mould growth, which threatens the building structural safety and indoor air quality. Pruteanu et al [ 26 ] analysed the occurring of condensation risk and its location in the outer wall made of wood-concrete blocks by the Glaser method, for different situations of arrangement and composition of the layers.…”
Section: Introductionmentioning
confidence: 99%
“…Xue et al [ 25 ] found inappropriate thermal insulation measures may exacerbate the humidity within the building envelope and further induce condensation and mould growth, which threatens the building structural safety and indoor air quality. Pruteanu et al [ 26 ] analysed the occurring of condensation risk and its location in the outer wall made of wood-concrete blocks by the Glaser method, for different situations of arrangement and composition of the layers.…”
Section: Introductionmentioning
confidence: 99%